THE CONVERGENCE OF TRADITIONAL WISDOM AND MODERN SCIENCE: A COMPREHENSIVE ANALYSIS OF OWL CAPABILITIES THROUGH MINAHASA CULTURAL KNOWLEDGE AND CONTEMPORARY RESEARCH - Winnetou J.I.Silap (International Journal of Social Science, 2025)
This comprehensive study presents an in-depth analysis of owl capabilities through an innovative interdisciplinary approach, combining traditional ecological knowledge from the Minahasa people of North Sulawesi, Indonesia, with contemporary scientific research. The study examines the sacred status of the Manguni (owl) in Minahasa culture alongside cutting-edge biological and aeronautical research into owl adaptations. Through extensive qualitative analysis of interviews with Minahasa cultural leaders, comprehensive literature review, and correlation with modern scientific findings, this research reveals remarkable parallels between traditional wisdom and scientific discovery. The study encompasses multiple disciplines, including ethnography, biology, biomechanics, neuroscience, and aerospace engineering, providing a holistic understanding of owl capabilities and their potential applications in modern technology